Mário de Andrade’s dance with shoulders: surupango of revenge - Vagner Camilo (Gragoatá, 2016)
This article analyzes "Danças" by Mário de Andrade, and the reflection the poet on the aesthetic and ethical dimensions of his verses, especially in letters addressed to friends, the first to read and discuss the poem. The change his mind about his own poem is examined in association with the doubts and conflicts experimented by poets and artists in the passage from the years 1920 to 1930.